Severe Iatrogenic Lutembacher Syndrome in a Young Male: Case Report and Literature Review (Global Journal of Medical Research, 2021)
Abstract not found
Keywords: atrial septal defect; mitral stenosis; lutembacher syndrome; iatrogenic; surgical treatment